DEPRESSION OF THE PERUVIAN ELDERLY ADULT AND ASSOCIATED SOCIODEMOGRAPHICAL VARIABLES, ANALYSIS OF ENDES 2017 - Baldeón Martínez, Paola (2019)
Objective: To determine the sociodemographic variables associated with depression in the elderly of Peru based on the information obtained through the Demographic and Family Health Survey (ENDES) of the year 2017 carried out by the National Institute of Statistics and Informatics (INEI). Methods: An observational, correlational and cross-sectional study that used a probabilistic sample of 4917 older adults (60 years and over). For the determination of depression in the population, the Patient Health Questionnaire (PHQ) of 9 questions included in the health questionnaire in the mental health section of ENDES 2017 was used as an instrument. Results: The prevalence of depression in the Peruvian elderly in 2017 was 14.2%. As sociodemographic variables associated with depression were the female sex [OR 1.995 (1.684 -2.364)]; lack instruction [ORaj 2.524 (2.126-2996)]; the age over 75 years [ORaj 1.763 (1.494 2.080)]; live in a rural area [ORaj 1.410 (1.198-1.659)]; and be poor [ORaj 1.456 (1.229 - 1.724)]. It was not associated with disability (p = 0.704). [ORaj 1.103 (0.663-1835)]. Conclusion: It was concluded that the prevalence of depression in the Peruvian adult is high. Among the sociodemographic variables that were identified as risk factors for presenting depression were female sex, lacking education, age over 75, living in rural areas and being poor.